Electron transport in quantum well heterotransistors - Москалюк, Владимир; Тимофеев, Владимир; Куликов, Константин (SWorldJournal, 2020)
The paper presents an analysis of electron transport processes in quantum wells of submicron heterostructural transistors. Techniques for modeling processes in nanoheterostructures have been developed, considering specific quantum effects and scattering